COMPACTNESS VERSUS REGULARITY IN THE CALCULUS OF VARIATIONS - Faraco, D; Kristensen, J (2012)
In this note we take the view that compactness in L p can be seen quantitatively on a scale of fractional Sobolev type spaces. To accommodate this viewpoint one must work on a scale of spaces, where the degree of differentiability is measured, not by a power function, but by an arbitrary function that decays to zero with its argument. In this context we provide new L p compactness criteria that were motivated by recent regularity results for minimizers of quasiconvex integrals. We also show how rigidity results for approximate solutions to certain differential inclusions follow from the Riesz-Kolmogorov compactness criteria.